Organizing Teacher Trainings for Local School Teachers to improve Teaching English Proficiency - Khujaeva Umida Makmud kizi; Avganova Gulfira Akbar kizi (Academia One Publishing, 2023)
This thesis aims to investigate the effectiveness of teacher training programs for local school teachers in improving their English language teaching proficiency. The study will assess the current state of English language teaching in local schools and identify areas where teachers require improvement. Additionally, the research will analyze the benefits of teacher training programs and their impact on the quality of English language teaching. To collect data from local school teachers and administrators, a mixed-method approach including surveys, interviews, and classroom observations will be used. The findings of this study will provide valuable insights into the effectiveness of teacher training programs and their potential to improve the quality of English language teaching in local schools. The research will also contribute to the development of effective strategies for organizing teacher training programs that can enhance the English language teaching proficiency of local school teachers
Keywords: Globalization; teacher trainings; smartboard